2020
DOI: 10.3389/fpls.2020.512844
|View full text |Cite
|
Sign up to set email alerts
|

MdMYC2 and MdERF3 Positively Co-Regulate α-Farnesene Biosynthesis in Apple

Abstract: α-Farnesene, a sesquiterpene volatile compound plays an important role in plant defense and is known to be associated with insect attraction and with superficial scald of apple and pear fruits during cold storage. But the mechanism whereby transcription factors regulate apple α-farnesene biosynthesis has not been clarified. Here, we report that two transcription factors, MdMYC2 and MdERF3 regulated α-farnesene biosynthesis in apple fruit. Dual-luciferase assays and Y1H assays indicated that MdMYC2 and MdERF3 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 50 publications
1
20
0
Order By: Relevance
“…In this study, 344 TFs consisting mainly of bHLH (76 genes), ERF (68 genes), MYB (52 genes), and WRKY (30 genes) were differentially expressed in response to H. armigera infestation ( Supplementary Table 4 ), which might contribute to the activation of different pathways of cotton plants to initiate sophisticated defense responses against H. armigera . TFs are involved in the biosynthesis of insect-induced volatile terpenes such as ( E )-β-caryophyllene in Arabidopsis thaliana ( Hong et al, 2012 ), ( E )-geraniol and valencene in Citrus sinensis ( Shen et al, 2016 ; Li et al, 2017 ), linalool in Freesia hybrida ( Yang et al, 2020 ), α-farnesene in apple ( Wang et al, 2020 ), ( E )-β-farnesene and ( E )-α-bergamotene in Zea mays ( Li et al, 2015 ). In cotton, GaWRKY1 is involved in the accumulation of δ-cadinene, the essential precursor in the gossypol biosynthetic pathway ( Xu et al, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, 344 TFs consisting mainly of bHLH (76 genes), ERF (68 genes), MYB (52 genes), and WRKY (30 genes) were differentially expressed in response to H. armigera infestation ( Supplementary Table 4 ), which might contribute to the activation of different pathways of cotton plants to initiate sophisticated defense responses against H. armigera . TFs are involved in the biosynthesis of insect-induced volatile terpenes such as ( E )-β-caryophyllene in Arabidopsis thaliana ( Hong et al, 2012 ), ( E )-geraniol and valencene in Citrus sinensis ( Shen et al, 2016 ; Li et al, 2017 ), linalool in Freesia hybrida ( Yang et al, 2020 ), α-farnesene in apple ( Wang et al, 2020 ), ( E )-β-farnesene and ( E )-α-bergamotene in Zea mays ( Li et al, 2015 ). In cotton, GaWRKY1 is involved in the accumulation of δ-cadinene, the essential precursor in the gossypol biosynthetic pathway ( Xu et al, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…A possible functional mechanism for the transcriptional repressor, ERF4 Previous studies have revealed that transcriptional activators often work together to form a synergistic activator complex to co-activate the expression of target genes (Sun et al, 2017;Yao et al, 2017;Wang et al, 2020;Zhang et al, 2020). Similarly, the plant repressor-type ERF TFs could recruit a corepressor to form a transcriptional repressor complex to synergistically block the transcriptional activation of their targets (Song et al, 2005;Zhou et al, 2017).…”
Section: Discussion Erf4 Positively Regulates Plant Growth By Promoti...mentioning
confidence: 99%
“…In Artemisia annua , overexpression of AaWRKY1 activates the expression of the key enzyme gene AaCYP71AV1 , thereby promoting the synthesis of artemisinin [ 55 ]. There were also many studies on the transcriptional regulation of bHLH transcription factors on the synthesis of sesquiterpenes, e.g., in Artemisia annua , overexpression of AaMICC2 transcription factors could improve the transcription level of AaCYP71AV1 and DBR2 genes [ 56 ], and in Malus pumila calli, overexpression of MdMYC2 and MdERF3 could significantly increase the transcription levels of MdHMGR2 and MdAFS , thereby increasing the synthesis of α-farneene [ 57 ]. However, it was unclear whether bHLH transcription factors in sandalwood were involved in transcriptional regulation of sandal sesquiterpene biosynthesis.…”
Section: Discussionmentioning
confidence: 99%